Integrating Wasthiyah Paradigm to the Issuance of COVID-19 Fatwa; Indonesia Case - Abdul Syatar; Achmad Abubakar; Muhammad Majdy Amiruddin; Chaerul Mundzir; Muammar Bakry (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
This article aims to integrate the wasathiyah paradigm of the Majelis Ulama Indonesia (MUI) fatwa product and the reality of religious social issues in the midst of the pandemic coronavirus disease 2019 (COVID-19).  This article adopts the normative-sociological approach. This article found that MUI fatwa products acted on strong aspects of moderation (wasathiyah), not just issuing fatwas. Various aspects of considerations (al-muwazanat) in fatwa products are marked by revealing strict arguments by expressing the opinions of the Qur'an, sunna, ijma, qiyas, the opinion of the Imam of the school and credible scholars and the views of other experts who support the issuance of fatwa in accordance with the needs of Muslims. The Washatiyah paradigm of MUI fatwa product is not influenced by political interests. It is in accordance with the maqashid al-shari'ah. The paradigm of MUI fatwa was reflected when recommending to Muslims to support and obey the government.